Analisis Karakteristik, Motivasi dan Kelembagaan Petani Cabai Terhadap Adopsi Inovasi di Kabupaten Tulungagung - Puspita Arum, Putri Pramesti; Mulyaningtyas, Ratna Dewi; Supriyono, Supriyono (Universitas Islam Kadiri, 2025)
This study aims to determine the influence of characteristics, motivation, and institutions of chili farmers on the adoption of innovation in Tulungagung Regency. The method used is a quantitative method. Data collection in this study was carried out by distributing questionnaires to chili farmers and calculated using SPSS Version 27. The results showed that the variables of characteristics, motivation, and institutions of chili farmers had a simultaneous effect on the adoption of agricultural sprinkle technology innovations. Farmer characteristics did not have a partial effect on the adoption of agricultural sprinkle technology innovations. This is because there are other factors that influence outside the study, namely operational factors (costs). Motivation has a partial effect on the adoption of agricultural sprinkle technology innovations. Farmers need to meet physiological, social and appreciation needs. Institutions have a partial effect on the adoption of agricultural sprinkle technology innovations. Agricultural institutions are an important means to increase farmer capacity through training, counseling, and sharing knowledge